First search for extremely high energy cosmogenic neutrinos with the IceCube neutrino observatory - Abbasi, R.; Abdou, Y.; Abu-Zayyad, T.; Adams, J.; Aguilar, J.; Ahlers, M.; Andeen, K.; Auffenberg, J.; Bai, X.; Baker, M.; Barwick, S.; Bay, R.; et al. (2010)
We report on the results of the search for extremely-high energy neutrinos with energies above 107GeV obtained with the partially (~30%) constructed IceCube in 2007. From the absence of signal events in the sample of 242.1 days of effective live time, we derive a 90% C.L. model independent differential upper limit based on the number of signal events per energy decade at E2?e+?µ+?t1. 4×10?-6GeVcm?-2?sec??-1sr?-1 for neutrinos in the energy range from 3×107 to 3×109GeV. © 2010 The American Physical Society.